2019
DOI: 10.1051/bioconf/20191201004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vineyard agricultural practices on the diversity of macroinvertebrates

Abstract: In Europe, agriculture represents the dominant land use and there is a substantial part of biodiversity associated with those habitats. Therefore, conservation studies should direct to agriculture fields aiming to minimize the biodiversity losses. Vineyards could play a key role in producing win-win solutions for agriculture and biodiversity conservation, as an entrance point of sustainable practices in agriculture management. This study aims to evaluate the influence of different agriculture practices on macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Growers must also take into account practicalities such as weather forecasts when using these products. New decision rules, management indicators, and decision support systems (DSS) are necessary to improve pest and disease management strategies [11,13,18]. Prophylactic measures also require a deeper analysis of the cropping system, increased planning, and more knowledge of the multiple processes occurring in the biological and agricultural system and their interactions [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…Growers must also take into account practicalities such as weather forecasts when using these products. New decision rules, management indicators, and decision support systems (DSS) are necessary to improve pest and disease management strategies [11,13,18]. Prophylactic measures also require a deeper analysis of the cropping system, increased planning, and more knowledge of the multiple processes occurring in the biological and agricultural system and their interactions [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the spatial scale used for the landscape quantification (i.e., distance from the crop) can determine the perceived effect of landscape on biodiversity (Whittaker et al, 2005). For example, some studies found that the abundance and diversity of beneficial arthropods within vineyard ecosystems are positively influenced by the large‐scale habitat heterogeneity (Franin et al, 2016; Pérez‐Bote & Romero, 2012; Ramos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increment of investigation in the last decades about biodiversity patterns and ecosystem services in vineyards (Paiola et al, 2020; Ramos et al, 2019), and the recognized role of Coleoptera as an important group of insects in this crop (e.g., Caprio et al, 2015; Geldenhuys et al, 2021; Jiménez‐García et al, 2019; Sáenz‐Romo et al, 2019; Thomson & Hoffmann, 2009; Thomson & Hoffmann, 2013), the knowledge about this group in Portuguese vineyards is still deficient. In Portugal, published data about Coleoptera mainly focus on the Demarcated Region of Douro and mostly on the ground beetle's community of vineyards (Carlos et al, 2019; Gonçalves et al, 2019; Sharma et al, 2018) or Coleoptera in other crops, such as olives, almonds, chestnuts or citrus (Benhadi‐Marín et al, 2011; Magro & Hemptinne, 1999; Santos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%